2017
DOI: 10.1002/pen.24596
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of bio‐based poly(pentamethylene oxamide)

Abstract: A novel bio-based polyamide, poly(pentamethylene oxamide) (PA52), with high molecular weight has been prepared from dibutyl oxalate and renewable monomer of 1,5-pentanediamine by a two-step polymerization procedure. The chemical structures are analyzed by Fourier transform infrared spectroscopy and proton nuclear magnetic resonance spectroscopy while the properties are evaluated by differential scanning calorimetry, thermogravimetric analysis, and water uptake measurements for the obtained PA52. The results re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Recently, polyoxamide (POA) has attracted much attention as high heat resistance polyamide . POA (‐[NH(CH 2 ) x NHCOCO] n ‐) is a kind of special polyamide with the shortest diacid‐unit in the main chain.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, polyoxamide (POA) has attracted much attention as high heat resistance polyamide . POA (‐[NH(CH 2 ) x NHCOCO] n ‐) is a kind of special polyamide with the shortest diacid‐unit in the main chain.…”
Section: Introductionmentioning
confidence: 99%
“…However, 1,5‐pentamethylene diamine is expensive and unstable in supply in present, limiting its large‐scale application. Preliminary study confirmed that the properties of poly (hexamethylene oxamide) (PA62) copolymers are comparable with PA52, and it is far better than PA46 . The raw materials of PA62 are cheap and easy to obtain.…”
Section: Introductionmentioning
confidence: 85%
“…Recently, a novel bio‐based POA, poly (penta methylene oxamide) (PA52), possessing high melting point (~300°C) and low saturated water absorption (<3 wt %), has been developed. Its comprehensive performance is far superior to the existing high heat‐resistant polyamide.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, polyoxamides with η int = 1.9 were prepared. Recently, much research on polyoxamides has been reported by utilizing this two‐step polymerization method, and high‐performance polyoxamides have been successfully synthesized 24–29 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, much research on polyoxamides has been reported by utilizing this two-step polymerization method, and high-performance polyoxamides have been successfully synthesized. [24][25][26][27][28][29] Comonomers are commonly utilized in polyamides to change the melt temperature and improve the processability. In this way, random copolyamides can be easily prepared.…”
mentioning
confidence: 99%